Studies on a thermostable alpha-amylase from the thermophilic fungus Scytalidium thermophilum - Aquino, A.C.M.M; Jorge, J.A; Terenzi, H.F; Polizeli, M.L.T.M (Applied microbiology and biotechnology, 2003)
An alpha-amylase produced by Scytalidium thermophilum was purified using DEAE-cellulose and CM-cellulose ion exchange chromatography and Sepharose 6B gel filtration. The purified protein migrated as a single band in 6% PAGE and 7% SDS-PAGE. The estimated molecular mass was 36 kDa (SDS-PAGE) and 49 kDa (Sepharose 6B). Optima of pH and temperature were 6.0 and 60 degrees C, respectively. In the absence of substrate the purified alpha-amylase was stable for 1 h at 50 degrees C and had a half-life of 12 min at 60 degrees C, but was fully stable in the presence of starch. The enzyme was not activated by several metal ions tested, including Ca(2+) (up to 10 mM), but HgCl2 and CuCl2 inhibited its activity. The alpha-amylase produced by S. thermophilum preferentially hydrolyzed starch, and to a lesser extent amylopectin, maltose, amylose and glycogen in that order. The products of starch hydrolysis (up to 6 h of reaction) analyzed by thin layer chromatography, showed oligosaccharides such as maltotrioses, maltotetraoses and maltopentaoses. Maltose and traces of glucose were formed only after 3 h of reaction. These results confirm the character of the enzyme studied to be an alpha-amylase (1,4-alpha-glucan glucanohydrolase).